2020
DOI: 10.33545/gynae.2020.v4.i3c.597
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnancies with a morbid adherent placenta from a tertiary referral Centre in North India

Abstract: Morbid adherent placenta (MAP) is an abnormality of placental implantation that is an important cause of maternal and fetal mortality. The maternal mortality may reach up to 7% and is associated with multiple maternal morbidities e.g. massive transfusions, infections, urologic injuries and fistula formation. The present study was a retrospective observational study done to evaluate the profile and outcome of pregnancies diagnosed with MAP over three years. Forty nine patients were diagnosed with MAP. The incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Another study conducted at a local hospital in the same city quoted its incidence as 4.7 per 1000 deliveries 4 . Similar studies done in India and Bangladesh have shown its incidence of 1.2 and 2 per 1000 deliveries respectively 5,6 .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Another study conducted at a local hospital in the same city quoted its incidence as 4.7 per 1000 deliveries 4 . Similar studies done in India and Bangladesh have shown its incidence of 1.2 and 2 per 1000 deliveries respectively 5,6 .…”
Section: Discussionsupporting
confidence: 72%
“…Maternal morbidity of 60% and mortality of 7% have been reported worldwide in literature 5,11,17 . Whereas in this study maternal mortality was 4.4%, the cause was DIC and multi-organ failure secondary to hemorrhage which is consistent with another study carried out by Yasmeen et al in which 6.6% of patients with MAP died due to a similar cause 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation